Effects of chamber shapes on maneuverability and control property of endoscope-support soft actuators - Lu, Yuxi; Zhou, Zhongchao; Tortos Vinocour, Pablo Enrique; Kokubu, Shota; Igarashi, Tatsuo; Yu, Wenwei (Frontiers in Bioengineering and Biotechnology, 2023)
In Minimally Invasive Surgery (MIS), soft actuators, activated by fluid or gas, enhance endoscope maneuverability. The interaction between the soft actuators and the endoscopes, influenced by contact surface area, friction, and inherent endoscope stiffness, determines the bending property, response property, and stiffness adjustability-critical factors for a stable surgical view and disturbance resistance.Assuming the endoscope shape and the hollow part of the soft actuators for inserting the endoscope predetermined, the cross-sectional chamber shape is the main adjustable design component affecting the interaction. Previous research has explored its impact on bending capabilities, however, comprehensive effects on the interaction, response property and stiffness adjustability are less explored.Our study addresses this issue by systematically examining various chamber shapes within a novel bilateral symmetrical air chamber design. Through Finite Element Analysis and prototype testing, we find that wider chamber widths lead to larger friction forces, thereby enhancing the interaction and improving the bending property, response property, and stiffness adjustability.These findings emphasize the crucial role of chamber shape in designing soft actuators. They provide key insights for optimizing the design of endoscope-supporting soft actuators in MIS for handling actuator-endoscope interaction.